SWOT Analysis to Determine Competitive Strategy at PT. Tarindo - Aulia Ramadhanti, Nazwa (Siber Journal of Transportation and Logistics, 2023)
This study aims to determine a competitive strategy for PT. Tarindo. Through market analysis, competitors and the company's internal strengths, the strategy determined must be in accordance with the company's vision and mission and oriented towards competitive advantage. The practical implication of this research is the importance of adapting strategies to the ever-changing business and technological environment.